Construction of IGA-suitable Volume Parametric Models by the Segmentation–Mapping–Merging Mechanism of Design Features. (May 2022) - Chen, Long; Bu, Ningyuan; Jin, Yao; Xu, Gang; Li, Baotong
Abstract: Volumetric parameterization is the key and bottleneck issue in the current research of constructing complex models for isogeometric analysis(IGA). Many researchers used reconstruction methods to convert the models presented in the boundary form such as B-rep, constructive solid geometry(CSG) or the finite element(FE) meshes. In these methods, recognition and understanding of topology is a difficult and unavoidable issue. What is more, the reconstruction methods are not compatible with the current modeling methods and processes adopted in the prevailing CAD software. In this paper, a method is proposed to construct the complex volume parametric models based on the Segmentation–Mapping–Merging mechanism of the design features. The semantic feature network is obtained by the interactive input or the feature elements extracted from existing CAD models, which allows great geometric flexibility. Then the semantic feature network is partitioned into the geometric feature networks and the complete feature networks under the constraints of volume parametric modeling. Each complete feature network is constructed as a volume parametric patch by volume parametric mapping. Finally, the volume parametric patches are merged into a whole model and are adjusted to be suitable for IGA. Some complex shapes including the mechanical parts, free-form models are presented to verify the effectiveness, availability and robustness of our method. Graphical abstract: Highlights: A platform of integration design based on volumetric parameterization is put forward. A modeling mechanism called segmentation–mapping–merging for the volume parametric patches is studied. The proposed method is realized and verified on the complex three-dimensional models.